Cancer of esophagus and GE junction– a long-term follow-up results - Binay Thakur (Society of Surgeons of Nepal, 2016)
Background:  Esophageal and GE Junction malignancies are diagnosed late and the long-term outcome is still suboptimal. We present our experience.